Labour reallocation dynamics in Germany during the COVID-19 pandemic and past recessions - Niklas Garnadt; Christina von Rueden; Esther Thiel (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2021)
How do recessions affect labour reallocation dynamics? Using data for Germany we document that gross job reallocation has been slightly countercyclical in the past and has increased slightly in previous recessions. This mild countercyclicality results from procyclical job creation rates and slightly more countercyclical job destruction rates. The recession caused by the COVID-19 pandemic has been atypical in this regard. While the reallocation of workers within sectors declined due to lower hiring and separation rates, the reallocation of workers between sectorssurprisingly increased. Finally, we document that short time work likely played a substantial role in reducing separation rates, thus dampening the reallocation process during the COVID-19 recession in Germany.
Keywords: 330